Multilayer social networks - Dickison, Mark E., 1981-
"This book covers the modeling, analysis and mining of systems made of multilayer social networks, from groups of individuals connected through different types of relationships to large systems of multiple online social network sites. A range of practical and theoretical topics are covered, from data collection, pre-processing, measuring and mining to theoretical models behind the evolution of interconnected social networks and dynamical processes like information spreading"--